Metapopulation dynamics of roseate terns: Sources, sinks and implications for conservation management decisions. Issue 1 (23rd October 2018) - Seward, Adam; Ratcliffe, Norman; Newton, Stephen; Caldow, Richard; Piec, Daniel; Morrison, Paul; Cadwallender, Tom; Davies, Wesley; Bolton, Mark
Abstract: Habitat management to restore or create breeding sites may allow metapopulations to increase in size and reduce the risk of demographic stochasticity or disasters causing metapopulation extinction. However, if newly restored or created sites are of low quality, they may act as sinks that draw individuals away from better quality sites to the detriment of metapopulation size. Following intensive conservation effort, the metapopulation of roseate tern ( Sterna dougallii ) in NW Europe is recovering from a large crash in numbers, but most former colonies remain unoccupied and hence are potential targets for restoration. To inform conservation efforts, we studied the dynamics of this metapopulation with a multistate integrated population model to assess each of the three main colonies for important demographic contributors to population growth rate, source/sink status and possible density dependence. All three study colonies are managed for roseate terns (and other tern species) in similar ways, but the demographic processes vary considerably between colonies. The largest colony is a source involved in almost all dispersal, and its growth is determined by survival rates and productivity. Productivity and juvenile apparent survival at the largest colony appear to be density‐dependent. Although the mechanisms are unclear, this may provide an increasing impetus for emigration of recruits to other colonies in future. The smallest of the three colonies is a sink, relying on immigration for its growth. Simulation models suggest the metapopulation would be c . 10% larger in the absence of dispersal to the sink colony. This work indicates that, due to variable site quality, aims to enhance both distribution and size of metapopulations may be mutually exclusive. In this case, before future attempts to encourage recolonisation of former sites, assessments of site suitability should be undertaken, focusing on food availability and isolation from predators to maximise the likelihood of attaining levels of productivity and survival that avoid creation of a sink population to the detriment of the overall metapopulation size. Abstract : The authors' multistate integrated population model (IPM) builds on IPMs found in the literature, by allowing the analysis of population growth, productivity, survival and dispersal at multiple colonies simultaneously. The model outputs can be used to guide management, such as colony restoration.